STRATEGI KEPALA MADRASAH DALAM PENINGKATAN DIGITALISASI PEMBELAJARAN DI MAN 1 JOMBANG - Perdi Dwi Pranata; Moh. Syamsyul Falah (STKIP Pesisir Selatan, 2026)
This study comprehensively investigates the strategic management of a madrasah head—encompassing formulation, execution, and evaluation—in accelerating digital transformation to escalate academic quality at MAN 1 Jombang. Employing a descriptive qualitative design, data collection relied on in-depth interviews, classroom observations, and curriculum document analysis involving administrators, teachers, and staff. The findings demonstrate leadership success in pioneering a pilot Digital Class project integrated with the